2017
DOI: 10.1371/journal.pone.0178033
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological investigation of the relationship between common lower genital tract infections and high-risk human papillomavirus infections among women in Beijing, China

Abstract: BackgroundThe incidence of lower genital tract infections in China has been increasing in recent years. The link between high-risk human papillomavirus (HR-HPV) and other sexually transmitted diseases (STDs) remains unclear.MethodsFrom March to October 2014, gynecological examinations and questionnaires were conducted on 1218 married women. Cervical secretions and vaginal swab specimens were tested for Chlamydia trachomatis (CT), Neisseria gonorrhoeae (NG), Ureaplasma urealyticum (UU), yeast, clue cells and HR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(61 citation statements)
references
References 39 publications
5
48
1
7
Order By: Relevance
“…However, several recent studies investigating the role of cervical co-infections of Ureaplasma spp. and other STIs in association with hrHPV, have supposed that these could be possible cofactors interacting with HPV in the development of precancerous and cancerous cervical lesions [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…However, several recent studies investigating the role of cervical co-infections of Ureaplasma spp. and other STIs in association with hrHPV, have supposed that these could be possible cofactors interacting with HPV in the development of precancerous and cancerous cervical lesions [31][32][33][34][35][36].…”
Section: Discussionmentioning
confidence: 99%
“…BV was described in 20% of the ASC-US group and 25% of the ASC-H group. Other studies have also reported a predominance of BV but with different frequencies [19,20] . The characteristic "clue cells" may hide the atypical character of real lesions, and the satisfied criteria would be indicative of ASC.…”
Section: Discussionmentioning
confidence: 83%
“…When correlating the vaginal microbiota with HR-HPV in ASC-US cytology, we observed a predominance of BV, but there was no statistically significant difference with HR-HPV positivity. Other studies have pointed out an association between BV and HR-HPV infection, suggesting BV may be a cofactor for squamous intraepithelial lesions due the action of pathogens causing inflammatory processes and microabrasions on the cervical epithelium [19] . A significantly higher frequency for Candida spp.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…urealyticum üretrit, vajinit, servisit, spontan düşük ve infertilitenin sık görülen sebebi olup, vajinal kolonizasyon kadınlarda %40-80 arasında görülür. U. urealyticum infeksiyonunun HR HPV ve servikal kanserin patogenezi ile ilişkili olduğu, hem hücresel anomalileri başlatmada hem de viral kalıcılığında rol oynayabileceği birçok çalışmada bildirilmiştir [20,26] . U. urealyticum infeksiyonu HPV pozitif kadınlarda %30.5 (61/200) oranında, HPV negatif kadınlarda %23 (23/100) oranında tespit edilmiştir.…”
Section: Materyal Ve Metodunclassified